PENGARUH PENAMBAHAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) SEBAGAI STABILIZER TERHADAP DAYA LELEH DAN OVERRUN ES KRIM - Ahmad Nadirsyah; Ellyna Hafizah; Yudha Irhasyuarna (Journal of Food Technology and Agroindustry, 2023)
Stabilizer is an ingredient of polysaccharides to prevent the crystals in the ice cream from expanding which affects the melting power and overrun of the ice cream. The choice of stabilizer also affects the texture and taste of the ice cream. White oyster mushrooms are known to contain beta-glucan substances from polysaccharides that are able to bind to air so that they can be used as alternative natural stabilizers. Therefore, this study aims to determine the effect of adding white oyster mushrooms as a stabilizer to the melting and overrun power and organoleptic properties of ice cream. The research method used is a mixed method in the form of observational and experimental methods. The results of the overrun test using one way ANOVA and post hoc tests on a sample of 100 grams showed significant differences between treatment groups, especially in the sample group of 0% and 0.5%. The results of the melting power test using one way ANOVA and post hoc tests on a sample of 10 grams had a significant difference in the overall sample, while organoleptic testing with the kruskall-Wallis and Mann-Whitney test showed that there was an influence between treatment groups on texture factors, especially the 0.1% sample and 0.5% and significant differences in taste factors, especially the 0% and 0.3% groups, the 0% and 0.5% groups, the 0.1% and 0.3% groups, the 0.1% and 0.5% groups. . The overall research results have complied with SNI No. 01-3713-1995 regarding the melting range of ice cream, which is 15-25 minutes, the overrun value ranges at 30 - 50% for the household scale.